Molecular Identification of Entameba Histolytica and Entameba Dispar in Patients with Diarrhea (Journal of Pharmaceutical Negative Results, 2022)
Entamoeba histolytica and Entamoeba dispar (also known as E. dispar) are responsible for the parasitism of around ten percent of the world's population. However, only ten percent of those infections cause symptoms. Using Real-Time PCR methods, the purpose of the research was to distinguish between the two strains of E. histolytica and E. dispar. The current study was carried out between the 1st of November 2020 and the 20th of March 2021. We collected stool samples from 455 patients of varying ages (1-60 years) who presented themselves at pediatric clinics in Kirkuk city complaining of diarrhea and/or stomach discomfort. These patients sought treatment at one of the clinics. RTPCR analysis was then performed on the samples that were found to be positive by microscopy. Stool samples were collected using sterile wide mouth screw cap containers. Fresh samples were analyzed using light microscopy, and after that, samples were stored in the refrigerator until they were analyzed using ELISA and PCR. The assay for the detection of the Entamoeba histolytica genome was carried out with the assistance of a specific Real-Time PCR, the Kestrel-realtime Entamoeba histolytica qPCR kit, and the FAM channel for the detection of target pathogen amplification. According to the findings of the study, 93 (or 48.69%) of the total wet mount positive patients were infected with trophozoites, and 70 (or 36.65%) were infected with both cysts and trophozoites. 14.89% of patients with dysentery were infected with E. histolytica who were diagnosed by PCR. The high incidence of positive cases were males at a rate of 28.57%, compared with 23.46% of females who were E. histolytica / E. dispar positive. The finding was significant. Only 37.36% of the total positive wet mount patients were suffering from dysentery, whereas all E. histolytica infected patients who were diagnosed by PCR were suffering from dysentery and 95.45% of them were suffering from abdominal pain. PCR was used to diagnose all E. histolytica infected patients.